2011
DOI: 10.1177/147323001103900625
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Infradian and Circadian Rhythms in the Persistent Vegetative State

Abstract: This retrospective study investigated the circadian and infradian characteristics of blood pressure and heart rate in 26 patients with traumatic head injury in a persistent vegetative state (PVS). Systolic and diastolic blood pressures and heart rate were measured every hour for the first 240 h (10 days) following hospital admission. These data were analysed for the presence of circadian and infradian rhythms using the least-squares fit of the cosine function with the single cosinor method. Infradian rhythms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Isono et al [14] also reported an absence of EEG sleep-wake changes in 4 out of 12 VS patients. High variability has also been observed in other physiological circadian rhythms in VS and MCS, including body temperature and hormone levels [15,16], blood pressure and heart rate [16,17], and sleep-related erections [18]. Circadian-like variations in arousal have also been reported in both VS and MCS patients, as indexed by fluctuating behavioral abilities across the day [19].…”
Section: Introductionmentioning
confidence: 99%
“…Isono et al [14] also reported an absence of EEG sleep-wake changes in 4 out of 12 VS patients. High variability has also been observed in other physiological circadian rhythms in VS and MCS, including body temperature and hormone levels [15,16], blood pressure and heart rate [16,17], and sleep-related erections [18]. Circadian-like variations in arousal have also been reported in both VS and MCS patients, as indexed by fluctuating behavioral abilities across the day [19].…”
Section: Introductionmentioning
confidence: 99%
“…Circadian and multiday cycles in human physiology have been described in normal health and disease [24][25][26][27][28][29][30][31] . Of particular interest multiday cycles, including circaseptan 32 (weekly) and circamonthly 33 cycles, have been identified in the regulation of immune, 26 endocrine, 28,34 metabolic, 35 and cardiovascular 36,37 systems, in human behavior, 32 as well as in brain excitability 17,20 and seizure risk. [2][3][4][5][6]12 Prior work on naturally occurring human and canine epilepsy has established that multiday cycles are common, with evidence for grouplevel circa-weekly, bi/tri-weekly, and monthly cycles.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study examining circadian rhythm variables of 3 UWS patients', including systolic blood pressure, diastolic blood pressure and heart rate. The authors report circadian periods of 24.25 h, 24.18 h, and 24.14 h [15]. In studies on healthy participants where environmental cues were controlled, the circadian period changes to something close to the free-running period [11,[17][18][19].…”
Section: Opinionmentioning
confidence: 99%
“…This free-running rhythm deviates from its normal cycle and it is usually longer than 24 h, around 24.18 h [11][12][13]. In fact, circadian rhythms of electrophysiology, skin temperature, hormone secretion, as well as blood pressure and heart rate [14,15] have been observed in some patients with UWS and MCS. However, when exposing to monochromatic light during night, MCS patients and healthy person displayed lightinduced suppression of melatonin but patients in UWS didn't displayed it [16].…”
Section: Opinionmentioning
confidence: 99%